Analisis Metode Penilaian Siswa pada Kurikulum Berbasis Kompetensi - Khofifah Indah T; Aribah Capah; Fitri Mardayanti; Septi Qorima Sitorus; Agum Budianto; Laurensia M. Perangin Angin (Lembaga Pengembangan Kinerja Dosen, 2025)
This study will analyze how the implementation of teacher assessment methods for students in the competency-based curriculum (KBK) with a focus on implementation at the primary school level. This study, using a literature review method using a qualitative approach, examined various literature sources from 2019-2023 to identify the characteristics, challenges, and strategies to improve the KBK assessment method. The results showed that the KBK uses extensive and authentic reviews to highlight students' skill attainment, both individually and classically. The main challenges to implementation include teacher time limits, difficulties in determining indicators and defining criteria, lack of training, and differences in student characters. Recommended improvement strategies are to enhance teachers' skills through continuous training, development of standardized assessment instruments, use of technology in the assessment process, and collaboration among stakeholders. This study provides a comprehensive overview of KBK assessment practices and solutions to optimize implementation in schools.